1995
DOI: 10.1007/s002800050342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium thiosulfate on the pharmacokinetics of unchanged cisplatin and on the distribution of platinum species in rat kidney: protective mechanism against cisplatin nephrotoxicity

Abstract: To investigate the mechanism underlying the protective effect against cisplatin (CDDP) nephrotoxicity of its antidote, sodium thiosulfate (STS), the effects of STS on the pharmacokinetics of unchanged CDDP and on the distribution of unchanged CDDP and high and low molecular mass metabolites (fixed and mobile metabolites) in the kidney 1 min after a bolus injection of CDDP (5 mg/kg) to rats were studied. A decrease in the plasma concentration of unchanged CDDP and an increase in the plasma concentration of mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to the pharmacokinetic study by Nagai, Hotta, and Yamamura (1995), about 35% of the dose has been excreted in the urine over 90 minutes after the CDDP injection to rats, and this has been detected mainly as unchanged CDDP. Because the electrophilic DNA-reactive form of CDDP is divalent cation Pt(NH 3 ) 3 2+ , the monitoring of unchanged CDDP is very important in pharmacokinetic study as well as in prognosis of chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…According to the pharmacokinetic study by Nagai, Hotta, and Yamamura (1995), about 35% of the dose has been excreted in the urine over 90 minutes after the CDDP injection to rats, and this has been detected mainly as unchanged CDDP. Because the electrophilic DNA-reactive form of CDDP is divalent cation Pt(NH 3 ) 3 2+ , the monitoring of unchanged CDDP is very important in pharmacokinetic study as well as in prognosis of chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium thiosulfate binds covalently to the electrophilic platinum, rendering the platinum inactive. 17–21 Elferink et al 17 reported that sodium thiosulfate reacts irreversibly with cisplatin to form Pt(S 2 O 3 ) 4 and that sodium thiosulfate must be administered before the administration of cisplatin for neutralization. More than 100 published reports have identified a protective effect of sodium thiosulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium thiosulfate, which neutralizes cisplatin, enables us to administer massive cisplatin doses directly to feeding arteries of the tumor because it mitigates systemic side effects, such as myelosuppression and renal dysfunction. [19][20][21] Fortunately, none of the patients presented with leukopenia or renal dysfunction before treatment in this study, and we could safely use cisplatin in all subjects. We observed mild leukopenia in only 1 patient who received Taxotere combined with cisplatin.…”
Section: Discussionmentioning
confidence: 99%